Parkinson's disease: the nutrition perspective. Issue 1 (4th March 2022) - Ó Breasail, Mícheál; Smith, Matthew D.; Tenison, Emma; Henderson, Emily J.; Lithander, Fiona E.
Abstract : Parkinson's disease (PD) is the second most common neurodegenerative disease after Alzheimer's disease and affects about 1% of the population over the age of 60 years in industrialised countries. The aim of this review is to examine nutrition in PD across three domains: dietary intake and the development of PD; whole body metabolism in PD and the effects of PD symptoms and treatment on nutritional status. In most cases, PD is believed to be caused by a combination of genetic and environmental factors and although there has been much research in the area, evidence suggests that poor dietary intake is not a risk factor for the development of PD. The evidence about body weight changes in both the prodromal and symptomatic phases of PD is inconclusive and is confounded by many factors. Malnutrition in PD has been documented as has sarcopaenia, although the prevalence of the latter remains uncertain due to a lack of consensus in the definition of sarcopaenia. PD symptoms, including those which are gastrointestinal and non-gastrointestinal, are known to adversely affect nutritional status. Similarly, PD treatments can cause nausea, vomiting and constipation, all of which can adversely affect nutritional status. Given that the prevalence of PD will increase as the population ages, it is important to understand the interplay between PD, comorbidities and nutritional status. Further research may contribute to the development of interventional strategies to improve symptoms, augment care and importantly, enhance the quality of life for patients living with this complex neurodegenerative disease.